Endometriosis: Classification, Risk factors, Diagnosis and management - Review of Literature - Kamińska, Monika Anna; Czach, Magdalena; Dąbrowska, Anna; Gonciarz, Marta Justyna; Zaliwska, Dominika; Paduszyńska, Natalia; Strojny, Agnieszka Aleksandra; Adamiec, Dominika Karolina; Kraszkiewicz, Adrianna; Do, Monika Kienanh (Quality in Sport, 2024)
Endometriosis is an oestrogen-dependent disease characterised by the presence of the endometrial tissue outside its normal location. Three types of endometriosis are distinguished: ovarian, peritoneal, and deeply infiltrating [1,2]. The literature reports that 6-15% of the general female population suffers from endometriosis. This disease occurs mainly in women of reproductive age, but also in young women and postmenopausal women [3]. Symptoms of endometriosis include periodic pain that becomes constant, very painful menstruation, painful intercourse, as well as painful micturition or defecation. Endometriosis is present in up to 35-50% of women diagnosed with infertility. In diagnosing endometriosis, laparoscopy is of utmost importance, as it allows for simultaneous treatment of the condition. Laparoscopy should be preceded by a thorough medical history and imaging diagnostics such as ultrasound or magnetic resonance imaging (MRI). The treatment of endometriosis is divided into pharmacological and surgical methods, which can be either conservative or radical. The type of treatment used depends on the patient's age and reproductive desires, the symptoms present, and the form of the disease. A proper diet and lifestyle play a significant role in the treatment of endometriosis.